Diplomasi Budaya Inggris Melalui Grup Musik One Direction di Indonesia - Abdullah Azzam, Akmal; Setiawan, Asep (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
This study explores the United Kingdom's cultural diplomacy through the boy band One Direction in Indonesia as a form of soft power implementation in international relations. Using a descriptive qualitative approach through literature review and content analysis, this research examines how One Direction serves as an effective instrument of cultural diplomacy by introducing British cultural values to Indonesian society. The 2015